2004
DOI: 10.1172/jci20518
|View full text |Cite
|
Sign up to set email alerts
|

Gluco-incretins control insulin secretion at multiple levels as revealed in mice lacking GLP-1 and GIP receptors

Abstract: The role of the gluco-incretin hormones GIP and GLP-1 in the control of β cell function was studied by analyzing mice with inactivation of each of these hormone receptor genes, or both. Our results demonstrate that glucose intolerance was additively increased during oral glucose absorption when both receptors were inactivated. After intraperitoneal injections, glucose intolerance was more severe in double-as compared to single-receptor KO mice, and euglycemic clamps revealed normal insulin sensitivity, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 52 publications
7
99
2
2
Order By: Relevance
“…As regard with the incretin effects of GIP, although, we did not perform oral glucose tolerance test to assess insulin response in this condition, studies performed on the same GIPR KO model that we used revealed that these animals are hypoinsulinemic in response to oral glucose challenge with a 40% reduction in plasma insulin level [17]. Insulin-deficient mice present a growth retardation that occurred predominantly in the fetal life with a decrease in bone formation [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regard with the incretin effects of GIP, although, we did not perform oral glucose tolerance test to assess insulin response in this condition, studies performed on the same GIPR KO model that we used revealed that these animals are hypoinsulinemic in response to oral glucose challenge with a 40% reduction in plasma insulin level [17]. Insulin-deficient mice present a growth retardation that occurred predominantly in the fetal life with a decrease in bone formation [40].…”
Section: Discussionmentioning
confidence: 99%
“…The background and generation of GIPR-deficient mice used in this study has been previously described [17]. Age-matched wildtype (WT) mice with the same C57BL/6 genetic background were used as controls (Harlan Ltd., Oxon, UK).…”
Section: Animalsmentioning
confidence: 99%
“…15 The hepatoportal sensor has been shown to control multiple physiological function. 5 Its activation stimulates first-phase insulin secretion, 16,17 increases hepatic glucose clearance, 18 stimulates, in an insulin-independent manner, peripheral tissue glucose uptake, 8,19 suppresses glucagon secretion (see below) and terminates feeding. 20,21 Thus, the combination of physiological as well as pharmacological and genetic studies has provided strong evidence for an important role of the hepatoportal sensor in the regulation of several homeostatic functions.…”
Section: Sites and Mechanisms Of Glucose Sensingmentioning
confidence: 99%
“…The GLP-1 receptor knock out mice (GLP-1R-/-) were in a mixed C57BL/6 and SV129 background and have been extensively characterized (Scrocchi et al, 1996). The GIP receptor knockout mice (GIPR -/-) were in a mixed C57BL/6 and SV129 background and have been extensively characterized (Preitner et al, 2004).…”
Section: Mice Models and Surgical Proceduresmentioning
confidence: 99%
“…A major characteristic of both incretin secretion and action is a strict glucose-dependency, which confers a therapeutic advantage for incretin-based approaches for the treatment of type 2 diabetes (Zander et al, 2002). Whereas considerable evidence supports a direct pancreatic effect of these peptides for the control of glucoseinduced insulin secretion, recent data support a role for extrapancreatic GLP-1 actions, including activation of the portal glucose sensor in the control of glucose homeostasis (Balkan et al, 1999;Knauf et al, 2005;Preitner et al, 2004). Activation of the portal glucose sensor depends on the absorption of glucose from the gut, triggering of glucose sensitive cells located in the enteric/hepatoportal area.…”
Section: Introductionmentioning
confidence: 99%